1960
DOI: 10.1149/1.2427639
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship between Brightness and Structure in Electroplated Nickel

Abstract: Nickel deposits of various brightnesses were plated from Watts baths containing several different addition agents. The as-plated surfaces of the deposits were examined by electron microscopy. All bright deposits had a very fine-grained structure. However, some fine-grained deposits showed surface crevices and were therefore not bright. A linear relationship between the fraction of the surface area having a roughness less than 0.15/~ and the logarithm of light reflected as measured with a photocell was found. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1960
1960
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 5 publications
1
22
0
1
Order By: Relevance
“…The relationship between the microstructure and brightness of electroplated nickel has been reported few decades ago [18]. This study has shown the effect of grain size, crystal texture, and surface morphology of nickel surface on its light reflecting capability.…”
Section: Introductionmentioning
confidence: 69%
“…The relationship between the microstructure and brightness of electroplated nickel has been reported few decades ago [18]. This study has shown the effect of grain size, crystal texture, and surface morphology of nickel surface on its light reflecting capability.…”
Section: Introductionmentioning
confidence: 69%
“…It is known that electroplating solutions are able to produce bright deposits which consist of crystallites smaller than the wavelength of visible light, 0?4 mm, 41,42 and having oriented grain structure. 43 A small grain size is a necessary, but not a sufficient, condition for brightness; likewise not all fine-grained deposits are bright. It has been found that the brightness depends on the degree to which morphological components of the surface and electrodeposits are in the same plane.…”
Section: Microhardness Reflectivity and Roughnessmentioning
confidence: 99%
“…Membrane morphology was analysed firstly by visual observation of the brightness [36] and secondly using SEM images. These images were obtained after Cu plating, after alloying and after the permeance tests, in order to check how the surface changed throughout the entire process.…”
Section: Membrane Characterizationmentioning
confidence: 99%